The use of the native language in the english classroom - Ayala Vásquez, Krisia Melany; Céron Ponce, Karla Yesenia; Ferrer Clará, Karla Estela; Sibrián, Rodolfo Alexander; Salazar Murcia, Pedro Antonio (San Salvador : Universidad de El Salvador, 2005)
The role of English as a second language is really important in the 21st century due to the world is in various stages of social, economic, and demographic transition. In every stage also in modern communication and technologies in most part of the world English is playing a competitive role. (Economist 1996). According to Catford (1959) native language (L1) would be the language of early-childhood acquisition also it is the language of dominant. The term foreign language (L2) implies two meanings: first, it refers to the chronology of language learning. A foreign language is any language acquired (or to be acquired) later than the native language. Secondly, foreign language is used to refer to the level of language command in comparison with a primary or dominant language. The ‘L1’/ ‘L2’ distinction was introduced by Catford in 1959 in which he expressed “We start from the common-sense distinction between ‘mother tongue’ or ‘native language’ and ‘second language’ or ‘foreign language’. As ‘primary language’ ‘L1’ and for the second ‘secondary language’ ‘L2’. We can tabulate the two sets of terms as follows: L1 (first language, native language, mother tongue, primary language, stronger language). L2 (second language, non-native language, foreign language, secondary language and weaker language)” This distinction became popular, particularly in Britain, in the sixties (Halliday, McIntosh, and Strevens 1967).
Tesis (Licenciatura en Idioma Inglés: Opción Enseñanza ) -- Universidad de El Salvador
Keywords: Ingles -- Enseñanza